Labor productivity and natural resources: an assessment at the national level in Honduras - Barbier, Bruno; Mejía, O.; Leclerc, Gregoire (International Center for Tropical Agriculture, 1999)
The study establishes the link between agricultural labor productivity and natural resources variables at the national level in Honduras. We show through spatial analysis of productivity and natural resources that the relationship between natural resource conditions and agricultural productivity is not as direct as one can imagine. Length of the rain)" season has a strong and quasi linear relation with income. Soil has little impact on productivity as well as slope and altitude since coffee production in the mountain has a strong relation on productivity. Access to the main cities and to the main seaports has little relation with productivity since some of the main cities are located in unproductive areas. Improving the small road network would have a more positive impact. The study suggests that good research and good policies can have a good impact on productivity.